The Role of The Government in Maintaining The Integrity of The Legal System in Indonesia in The Digital Era - Tajudinur Tajudinur; Lamijan Lamijan; Naya Amin Zaini (Jurnal Sosial Teknologi, 2026)
The advancement of digital technology has significantly altered many aspects of society, including Indonesia’s judicial system. The digitalization of law provides opportunities to increase efficiency, transparency, and accessibility, but it also presents challenges that may threaten the integrity of the legal system. The government plays a crucial role in maintaining the integrity of the legal system so that it continues to function fairly and reliably amid technological advancement. Various policies and regulations have been implemented to adapt the legal system to developments in the digital era, including aspects of electronic justice, data protection, and law enforcement against cybercrime. However, challenges in regulatory implementation and limited digital infrastructure remain obstacles to creating a legal system with integrity. The purpose of this study is to examine the government’s involvement in upholding the integrity of Indonesia’s legal system in the digital age and to identify the main obstacles to digital law enforcement. This study adopts a normative juridical method with an analytical approach to relevant laws and regulations, legal doctrines, and government policies related to the digital legal system. Through this method, the research focuses on examining existing legal norms and how they are applied to maintain legal integrity amid digital transformation. Furthermore, this research examines various strategies that the government can implement to strengthen a transparent, accountable, and effective digital legal system.